Review on shobhana varti - anajana netra kriya kalpa - Gurav Gajanand; S M Pasha (International Journal of Pharmacy and Analytical Research, 2022)
It is said that, loss of eye sight will immerse a person into the world of darkness so one should try to protect his vision. To achieve this many netra kriya kalpa are explained in ayurvedic classics. Anjana is one of the Netra kriya kalpa applying medicinal paste or powder to the inner side of the lid. Shobhana Varti Anjana is Lekhanajana explained in Gadanigraha and it is Indicated in Arma,Netra srava,Patala,Timir and Arbuda.